Biomateriales utilizados en los selles para las perforaciones en los tratamientos de endodoncia. Revisión de Alcance - Scoping Review. (2022)
Root perforations are a possible complication during root canal treatment, where the risk of failure in the affected tooth can increase, its prognosis will depend on the size of the perforation, the time lapse between the occurrence of the perforation and the repair, and the choice of repair material where it is another important factor in the prognosis, since it can be affected by its biocompatibility and the ability to provide a hermetic seal. Objective: To examine and map the biomaterials most effectively used for sealing perforations in endodontic treatments.